Maskulinitas dan Feminitas dalam Al-Qur’an (Implikasi Sosial Atas Karakter Negatif) - Ulvah Nur'aeni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
This paper presents an argument that the negative feminine and masculine characters possessed by every human being harm social aspects. This argument was obtained because there was a paradigm shift from a traditionalist view to a new concept that was born in the 1970s. The traditionalist paradigm explicates that masculine and feminine characters are seen as contradicting the dimensions of the character's personality, attractiveness, and roles that differentiate men and women. On the other hand, a concept that was born starting in the 1970s emphasized the opposite. For instance, Alfred B. Heilburn categorized masculine and feminine characters as having positive and negative sides. It was also upheld by Sachiko Murata who exposed that both masculine and feminine characters exist in every human being and both have good and bad characters that are not limited to men and women. Uniquely, masculine and feminine concepts, as well as positive and negative characters, are also contained in the Qur’an. Therefore, the Qur’an frees humans to choose masculine or feminine characters as well as positive or negative characters to represent their personality. After tracing verses in the Qur’an about masculine and feminine, both positive and negative, the researcher found that masculine and feminine characters that were considered negative have detrimental implications for personal and social life. Based on this description, the paper tries to examine and explore these social impacts by using the thematic method of the Qur’an and analyzed by the theory proposed by Sachiko Murata.